2017
DOI: 10.1371/journal.pone.0180171
|View full text |Cite|
|
Sign up to set email alerts
|

A cluster-randomized controlled study to evaluate a team coaching concept for improving teamwork and patient-centeredness in rehabilitation teams

Abstract: PurposeAlthough the relevance of interprofessional teamwork in the delivery of patient-centered care is well known, there is a lack of interventions for improving team interaction in the context of rehabilitation in Germany. The aim of the present study is to evaluate whether a specially developed team coaching concept (TCC) could improve both teamwork and patient-centeredness.MethodA multicenter, cluster-randomized controlled intervention study was conducted with both staff and patient questionnaires. Data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Qualitative findings also revealed the benefits of coaching included feedback, support, help with conflict management, and staying on task. These findings are consistent with those found in the study by Korner et al, 12 which revealed that team coaching improved team meetings and information exchange by improving willingness to accept responsibility derived from real-time feedback sessions. We similarly learned that feedback was important to the teams, which other studies have shown fosters reflective abilities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Qualitative findings also revealed the benefits of coaching included feedback, support, help with conflict management, and staying on task. These findings are consistent with those found in the study by Korner et al, 12 which revealed that team coaching improved team meetings and information exchange by improving willingness to accept responsibility derived from real-time feedback sessions. We similarly learned that feedback was important to the teams, which other studies have shown fosters reflective abilities.…”
Section: Discussionsupporting
confidence: 92%
“…The second paper involved a cluster-randomized controlled study designed to evaluate team coaching for improving teamwork and patient-centeredness among members of rehabilitation teams. 12 This study found that team coaching improved structured team meetings, information exchange and willingness to accept responsibility during feedback sessions that occurred in real-time. 12 Weaknesses in this paper include that the setting was limited to rehabilitation clinics and the study was conducted in Germany and is not generalizable to the United States.…”
Section: Introductionmentioning
confidence: 78%
“…153,154 Articulated through a PCR team Rehabilitation is often delivered by professionals from multiple disciplines; therefore, PCR approaches (and how the person experiences them) emerge from interactions with rehabilitation teams, not single professionals. 120,146,155 As such, PCR is contingent on individual professionals working within person-centered teams and is activated through team members systematically working together to address the persons' needs. 20 Optimally, all professionals who deliver interventions to the person demonstrate a shared commitment to PCR, 23,65,111 listen to the person, 82 and work toward common or articulated rehabilitation goals (beyond disciplinary-based agendas).…”
Section: Microsystemmentioning
confidence: 99%
“…The PO is better able to monitor and facilitate, as a team coach, teamwork capabilities. Team coaching concentrates on “working processes, team organization, distribution of roles and responsibilities and optimization of communication” (Korner et al , 2017, p. 4). This requires the PO to step away from the role as a team member to assess and optimize teamwork.…”
Section: Proposed Solutions For Mts Structures At Tcmentioning
confidence: 99%